Educating the Educators: Technology-Enhanced Mathematics Teaching and Learning - Leong Chee Kin (Southeast Asian Mathematics Education Journal, 2015)
Educational research has shown that teaching quality is one of the most important factors in raising student achievement. There is a compelling need for educators to keep abreast of the important developments that are taking place in educational arena. One of the educational areas that has massive development is the use of technology to enhance teaching and learning especially in mathematics. This development needs professional developmentamong educators. Being a regional science and mathematics education centre, the Southeast Asian Ministers of Education Organisation Regional Centre for Education in Science and Mathematics (SEAMEO RECSAM) has always been cognizant of the importance of these developments. Its training programmes are planned to incorporate these developments for in-service teachers, teacher educators and ministry of education mathematics officers. As the Centre's mandate aims to ensure that these participants from Southeast Asians countriesas well as those from outside the region are equipped with emerging educationaltechnology tools which can enhance teaching and learning of mathematics. This paper will share the Centre’s experiences in continuing professional development among mathematics teacher, teacher educators and officers from the ministry of education on educational innovation and technology.